User‐Centered Evaluation of Healthcare Information System Utilization: A Cross‐Sectional Study Integrating Acceptance Models - Fatemeh Aghilinasab; Mozhgan Tanhapour; Mohamad Jebraeily; Bahlol Rahimi (Health Science Reports, 2026)
ABSTRACT Background and Aims Despite the promising role of health information systems (HISs) in healthcare settings, they have not consistently met users' expectations. The current research aimed to investigate the extent to which the functions of a healthcare information system align with users' actual needs, while also identifying the factors that influence the system's utilization. Methods The study was conducted in 2021 at a tertiary university hospital in Urmia, Iran. It utilized a quantitative method with a descriptive, cross‐sectional design. Data were collected using a researcher‐made questionnaire from 32 administrative and clinical users of the hospital information system, employing a stratified sampling approach. We used SPSS version 27 for data analysis. Results Among the participants, paramedical staff have the highest level of satisfaction (mean difference = −0.42, 95% CI [−0.82, −0.02]) and system utilization (mean difference = −0.25, 95% CI [−0.46, −0.05]). Exploratory subgroup comparisons suggested potential differences in “familiarity with IT” across age groups (mean difference = 1.04, 95% CI [0.63, 1.46]) and work experience groups (mean difference = 0.53, 95% CI [0.06, 1.00]). The “user satisfaction” has a positive correlation with “system utilization” ( r = 0.830, p ‐value < 0.001), “matching the system with users' needs” ( r = 0.626, p ‐value < 0.001), and “training and supporting” ( r = 0.597, p ‐value < 0.001) variables. “Matching the system with users' needs” is also positively correlated to “system utilization” ( r = 0.713, p ‐value < 0.001). Conclusion This study is expected to improve HIS utilization, healthcare quality and productivity, and healthcare organizations' financial returns. Our findings have insightful implications for those interested in the successful implementation of HIS systems, including hospital managers, chief executive officers, health information technology personnel, and HIS vendors.